Embedding Islamic Values in Integer Problem Design: A Pedagogical Innovation to Elevate Student Engagement - Septi Ningtyas Cahyaningsih; Anis Munfarikhatin; Khumaeroh Dwi Nuraini (Jurnal Inovasi Pendidikan dan Sains, 2024)
This study aims to develop a set of integer mathematics problems that are integrated with meaningful contextual elements to enhance student engagement and learning interest. Using the Tessmer formative evaluation model, the development process included a preliminary study, self-evaluation, expert reviews, one-to-one testing, small group trials, and a field test with eighth-grade students at an Islamic-integrated junior high school in Indonesia. The resulting product consisted of 13 context-based integer word problems. Validation from content and pedagogical experts confirmed a high degree of validity (90%), while student responses indicated high practicality (96.7%). The effectiveness of the problem set was demonstrated by 94% of students achieving the minimum mastery level. Furthermore, a significant increase in student learning interest was observed, particularly in the emotional aspect, where the “joy” dimension rose by 69.62%. These results suggest that the integration of relevant, real-life contexts into mathematical problem design can significantly improve both student performance and motivation in mathematics classrooms